FAKTOR – FAKTOR YANG MEMPENGARUHI KEUNGGULAN BERSAING DALAM UPAYA MENINGKATKAN MARKET SHARE - Apriliani, Lydia; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2015)
The study aims to analyze the market share of the competitive advantage of the iPhone smartphone in mobile phone sales agents in Semarang. This study departs from the research problem is: "How to increase market share on Apple products?" A literature review conducted has led researchers to produce a model of research studies the relationship formed by four (4) variables: product quality, product innovation, price, competitive advantage and one (1) indicator is market share.          This research method using a technique of sampling purposive with sample as many as 100 respondents at a sales agent of mobile phone in Semarang. Analysis method used is an analysis of quantitative and qualitative analysis uses linear regression analysis double with SPSS. This analysis includes: test of validity and reliability, classic test assumptions, regression analysis double, the testing of hypotheses through t test and test f, determination and the coefficients (r2).            The results showed that in the first equation of product quality, product innovation and a significant positive effect on competitive advantage. For the second equation competitive advantage and price positive and significant impact on market share. Variable product innovation is the most dominant factor affecting the competitive advantage of 0.572 and the smallest factor affecting the market share is the price of 0216. Then through the F test can be seen that all the independent variables is feasible to test the dependent variable. Figures Adjusted R Square on the first equation 0.568, while the second equation by 0091. This shows bahwa56.8% competitive advantage can be explained by the variable quality of products and product innovation. While in the second equation indicates that 9.1% of market share can be explained by the competitive advantage and price variables. The rest can be explained by other variables outside of research.